Search for neutral Higgs bosons in multi-b-jet events in pp[over] collisions at sqrt[s]=1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
Data recorded by the D0 experiment at the Fermilab Tevatron Collider are analyzed to search for neutral Higgs bosons produced in association with b quarks. This production mode can be enhanced in the minimal supersymmetric standard model (MSSM). The search is performed in the three b quark channel using multijet triggered events corresponding to an integrated luminosity of 1 fb(-1). No statistically significant excess of events with respect to the predicted background is observed and limits are set in the MSSM parameter space.